Peningkatan Kemampuan Bertanya dan Pemecahan Masalah Peserta Didik SMA dalam Pembelajaran Fisika Melalui Problem Based Learning - Godelfridus Hadung Lamanepa; Isabel Coryunitha Panis (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
This study aims to improve the ability to ask questions and problem solving skills of learners in the learning of physics through Problem Based Learning. This research is a classroom action research with two cycles in learning using problem based learning. Data collection techniques used to determine the ability to ask is by observation while for problem-solving skills using the test. Subjects in this study were students of Senior High School X class at St. Seminary Rafael Oepoi Kupang Academic Year 2017/2018. The results showed that: (1) there was an increase in the ability to ask learners in the second cycle; (2) there is an increase of mean value of problem solving ability of learners gradually that is from 68 at initial test, 72 at cycle I and 77 in cycle II. Keywords— Questioning skills, Problem Solving skill, PBL